Agama dan Pengembangan Karakter Mahasiswa: Kajian Latar Belakang Agama dan Kearifan Lokal di Sulawesi Tengah - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Balai Diklat Keagamaan Bandung, 2024)
This study aims to learn how religious rituals and religious rituals and local wisdom of tribes in Central Sulawesi affect the characters of the character of university students. The importance of this research is its possibility to provide a deeper understanding of how these two components influence the nature of university students. This research uses a combined approach of case studies, surveys, and interviews to understand the impact of religious rituals and local tribal wisdom on the character of university students. A total of 44 respondents selected the heterogeneous technique, considering differences in domicile, religion, and study program at the FKIP, University of study program at the FKIP, University of Tadulako. The results showed that respondents' understanding of religious principles and how religious rituals affect their character. Participation in religious ceremonies can foster a sense of volunteering and a desire to do positive things for the community. It also increases the sense of care and empathy for others. A sense of empathy and care for local wisdom contributes to the formation of an inclusive campus environment. inclusive campus environment. Students can work together to celebrate and preserve cultural diversity, even though they come from different backgrounds. It is evident that strong empathy is a solid foundation for character development. Local wisdom in Central Sulawesi has played an important role in facilitating the coexistence of various ethnicities and religions in the academic world. Various ethnicities and religions are able to create an inclusive and harmonious academic environment by applying local wisdom.